ChemInform Abstract: Chiral Broensted Acid‐Catalyzed Enantioselective Synthesis of Isoindolinone‐Derived N(Acyl), S‐Acetals. Issue 23 (May 2016) - Suc, Josipa; Dokli, Irena; Gredicak, Matija
Abstract: The utility of this method is demonstrated in the synthesis of HIV‐1 reverse transcriptase inhibitor V (XII).